Analysis of the relationship between company characteristics and key audit matters disclosed - Ferreira, Catarina (2020)
The general objective of this study is to analyze whether the particularities of audited companies influence the volume of key audit matters (KAMs). Its specific objectives are to identify the number of KAMs disclosed by Brazilian companies and analyze the main factors associated with their disclosure. The paper aims to contribute to an area of investigation still lacking in studies that analyze the factors affecting KAM disclosure, which makes audit reports more individualized. The study contributes to understanding the main auditing issues in Brazilian companies that auditors consider relevant, by providing evidence on factors associated with their disclosure. This research is relevant for agencies that issue auditing standards and for financial information users. For issuers of auditing standards, the study is relevant because it identifies the factors associated with KAM disclosure, enabling it to be confirmed that the new audit report model has contributed to its destandardization. For financial information users, the study demonstrates that KAM disclosure varies from company to company, thus contributing to greater transparency of the audit report. Data were collected from the Audit Reports and Consolidated Financial Statements of the 447 Brazilian companies listed on the São Paulo Securities, Commodities, and Futures Exchange (BM&FBovespa), on December 31st of 2016, and an ordinary least squares (OLS) regression was applied to the defined model. The results show a positive relationship between the number of KAMs disclosed and both the auditor being a Big 4 and the complexity of the audited company. The auditor’s fees and auditor’s opinion being modified show a negative relationship with the number of KAMs. The article is relevant for companies, auditors, and regulatory and supervisory bodies as it identifies company characteristics that influence KAM disclosure and are determinants for the non-standardization of the auditor’s report.